COMPARATIVE ANALYSIS OF GENOTOXIC EFFECTS OF PORPHYRIN FeTOBut4PyP AT CELL AND ACELLULAR SYSTEMS IN COMET ASSAY (Proceedings of the YSU B: Chemical and Biological Sciences, 2007)
The genotoxicity of the new porphyrin FeTOEt4PyP was investigated at cell and acellular systems. Experimental cell and acellular systems used were based on Comet-assay. The differences in the sensitivity of two models presented are to reflect the different levels of their organisation. The approach applied may be recommended for the estimation of genotoxic effects of different agents and comparative analysis of role of cellular mechanisms in DNA damage.
Keywords: porphyrin FeTOEt4PyP; Comet-assay; genotoxic effects; sensitivity